Synthesis of nickel cobalt-codoped tin oxide nanoparticles from Psidium guajava with anticancer properties - Elderdery, Abozer Y.; Alzahrani, Badr; Alabdulsalam, Abdulrahim A.; Alanazi, Fehaid; Hamza, Siddiqa M. A.; Elkhalifa, Ahmed M. E.; Alhamidi, Abdulaziz H.; Mohamedain, A.; Subbiah, Suresh Kumar; Mok, Pooi Ling (Elsevier, 2022)
Metal oxide nanoparticles have been found to selectively target the tumor cells while non-toxic to the normal cells. Leukemia is one of the widespread and deadly cancers in adults, as well as the most common cancer in children. Recently, the nanoparticles have evolved as a simple, economic, effective, and ecologically sound strategy among the known nanoparticle synthesis techniques. In the present study, the structural, optical, and antibacterial effects of nickel cobalt-codoped Tin oxide nanoparticles (SnNiCoO2 NPs) formulated by the green process and the anticancer potential of SnNiCoO2 NPs in Molt-4 cells have been studied. The cytotoxic potential of the NPs against Molt-4 cells was estimated by MTT assay. The ROS and MMP levels were measured using fluorescent dyes and the changes in morphology and nuclei were noted using AO/EB staining. CAT, SOD, MDA, and GSH), and Proinflammatory Cytokines (TNF-α and IL1β) were also studied. The activity of caspase-3, −9, and −8 levels was examined to analyze the apoptotic mechanism. The XRD patterns of SnNiCoO2 NPs revealed a tetragonal structure. The SnNiCoO2 NPs was revealed a diameter of 126 nm by the DLS study. The morphology and elemental composition were studied using FESEM and EDAX spectra. In the FT-IR study, the O-sn-O stretching band was found to be 615 and 542 cm-1. The antimicrobial potential of the SnNiCoO2 NPs was examined against S. aureus, E. coli, and C. Albicans strains. A tremendous reduction in the viability of MOLT-4 cells at concentration-dependent mode witnessed the cytotoxic potential of the formulated NPs. The augmented ROS accumulation, depletion of MMP status, depleted antioxidants, and increased proinflammatory cytokines (TNF-α and IL1β) were noted on the NPs exposed cells. Furthermore, the increased expressions of caspase-3, −9, and −8 was also noted in the NPs treated MOLT-4 cells. Hence, the outcomes suggest that the formulated SnNiCoO2 NPs had remarkably potent antimicrobial and anticancer properties and could potentially prove beneficial in cancer treatment. Induces mitochondrial oxidative stress with nickel–cobalt-codoped tin oxide nanoparticles from Psidium guajava, which is a potential drug candidate for the antibiotic, antifungal, and anticancer activities of plant-based nanoparticles.